Perilaku Tokoh Utama Ama Ola dalam Cerpen Kabar di Malam Natal Karya Silvester Petara Hurint (International Forum of Researchers and Lecturers, 2025)
This study aims to describe the behavior of the main character Ama Ola in the short story